DnaG Primase-A Target for the Development of Novel Antibacterial Agents - Stefan Ilic; Shira Cohen; Meenakshi Singh; Benjamin Tam; Adi Dayan; Barak Akabayov (MDPI AG, 2018)
The bacterial primase—an essential component in the replisome—is a promising but underexploited target for novel antibiotic drugs. Bacterial primases have a markedly different structure than the human primase. Inhibition of primase activity is expected to selectively halt bacterial DNA replication. Evidence is growing that halting DNA replication has a bacteriocidal effect. Therefore, inhibitors of DNA primase could provide antibiotic agents. Compounds that inhibit bacterial DnaG primase have been developed using different approaches. In this paper, we provide an overview of the current literature on DNA primases as novel drug targets and the methods used to find their inhibitors. Although few inhibitors have been identified, there are still challenges to develop inhibitors that can efficiently halt DNA replication and may be applied in a clinical setting.